Hydatic cyst of the interpectoral space: about an observation - Gateño Yaffe, Nisso J (Cirugía del Uruguay, 2021)
One case, cluly documented, of hydatid cyst of the interpectoral cavity space, is presented. Its frequency, symptomatology and treatment are discussed.